Redistribution of efforts between the belts of four-belt towers - Yu. V. Krasnoshchekov; M. Y. Zapoleva (Вестник СибАДИ, 2024)
Introduction. The article presents the results of a study of the calculation features of four-belt towers depending on the direction of a wind action. The purpose of the article is to identify the conditions for the redistribution of forces in the belts of a grid tower under the action of a wind load along a diagonal of a square section and loss of stability of the most compressed belt. The attention is drawn to the fact that with the development of the process of loss of stability of the compressed belt, it does not turn off completely, but continues to partially carry the load. The data obtained indicate that it is possible to calculate all the elements and the tower as a whole according to a single scheme A (a wind pressure on the face of the tower), taking into account the coefficient of the wind angle. In the calculation example, graphical dependences of the forces in the belts on the resistance are obtained.Materials and methods. A feature of the calculation of four-belt towers is the dependence of the forces in the belts on the direction of the wind load. According to the maximum compression forces under the action of wind on the rib and bending of the tower, the cross section and length of the panel of all belts are assumed. The resulting reserve of strength and rigidity of the tower of the two belts in the limiting state adopted in the design standards is not possible to implement, since the limiting state of the compressed belts is assumed by the condition of stability in the form of bifurcation. If the limiting state of the belt panels is assumed according to the condition of bearing capacity in the supercritical stage of deformation, then it is possible to calculate the redistribution of compressible forces to reserve belts. In the given example, the criterion of resistance is used to analyze the redistribution of forces between the belts when the stability of the most compressed belt is lost according to the design scheme B (wind pressure on the tower rib).Conclusions. The results of modelling the tower calculation in the LIRA PC showed that taking into account the supercritical deformation of the compressed belt in the elastic stage makes it possible to calculate all the elements and the tower as a whole according to a single scheme A (a wind pressure on the face of the tower), taking into account the coefficient of the wind angle. At the same time, even with an increase in the coefficient value to 1.4 (instead of 1.2), the calculation efficiency is greater than the traditional one. The results of the study may be the basis for reducing the estimated length of the elements of the most compressed belt according to the calculated scheme B.